Crises and Policy Responses within the Political Trilemma: Europe, 1929-1936 and 2008-2011 - Nikolaus Wolf (European Historical Economics Society (EHES), 2012)
The recent debate on the Eurozone failed to appreciate a particular characteristic of European crisis experiences, namely their fundamentally political character. To make my argument, I borrow from Dani Rodrik (2000) the framework of a "political trilemma" between cross-border economic integration, national institutions and democracy (in the sense of mass politics) and discuss its relation to the more commonly known "macroeconomic trilemma" as well as some limitations of the framework. The recent experience of a European debt crisis and the experience of Europe's Great Depression can be interpreted as a "political trilemma": both reflect the problem of designing effective policy responses to major economic shocks within the environment of deep economic integration across political boundaries and the regime choices that this involves. Within this framework I highlight some aspects of the 1930s that are informative to the policy choices in Europe today. Once we accept that some policy choices should be avoided, attention should be shifted to the remaining options and the obstacles that prevent their implementation, notably the challenge to transform democracy beyond national borders.
Keywords: F42; F50; N14; 330; political trilemma; great depression; euro-crisis